Burnout in Canadian Radiology Residency: A National Assessment of Prevalence and Underlying Contributory Factors. Issue 1 (February 2020) - Ferguson, Craig; Low, Gavin; Shiau, Gillian
Objective: To determine burnout prevalence in Canadian radiology residency and identify contributing factors. Materials and Methods: A prospective 57-item survey, including the 22-item Maslach Burnout Inventory-Health Sciences Survey, was sent to all Canadian radiology residents, with a total resident population of 359. The association between emotional exhaustion (EE), depersonalization (DP), and personal achievement (PA) scores with items in the survey was performed. Continuous data were evaluated using the Student t test for comparing the means between the 2 groups or the analysis of variance test for comparing the means between at least 3 groups. Spearman correlation coefficient was performed when evaluating ordinal categorical data. Results: Response rate is 40.1% (n = 144); 50.7% of residents demonstrate high EE, 48.6% demonstrate high DP, and 35.9% demonstrate low PA. Being unhappy with residency and with radiology as a career is associated with burnout ( P < .001). Age, sex, marital status, and children have no impact on burnout. More hours worked is associated with higher EE ( P = .025) and DP ( P = .004). In all, 47.2% residents experienced intimidation or harassment. Feeling unsupported by staff radiologists is associated with higher EE ( P < .001), higher DP ( P = .001), and lower PA ( P = .008). In all, 45.1% of residents have poor work–life balance, and those residents demonstrate higher EE ( P < .001), higher DP ( P = .006), and lower PA ( P = .01). In all, 25% of residents identify poor education-service balance in their residency, and those residents have higher EE ( P < .001), higher DP ( P = .042), and lower PA ( P = .005). Conclusion: This study demonstrates significant burnout in Canadian radiology residents with major contributory factors identified.